Construction and validation of indicators for nursing management in blood transfusion - Daiana de Mattia; Dulcinéia Ghizoni Schneider; Francine Lima Gelbcke; Maria Manuela Frederico Ferreira; Edson Pacheco Paladini; Jose Luís Guedes dos Santos; Marcela Ganzella Sisdelli (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to construct and validate indicators for nursing management in blood transfusion. Methods: methodological study that involved the creation of technical sheets of indicators for nursing management in blood transfusion and their validation by 17 nurses working in Brazilian transfusion agencies. Data analysis was performed using descriptive statistics, content validity index and calculation of the percentage of agreement. Results: 27 indicators were validated for nursing management in blood transfusion, with a content validity index higher than 0.80 and a percentage of agreement higher than 80%. These indicators were organized into the categories structure, process and results, according to the environment evaluated. Conclusions: the established indicators present evidence of content validity, allowing their application in nursing management in the transfusion process, promoting continuous improvement of nursing team practices and strengthening transfusion safety.